Re-Orienting the Novel (KULT_online, 2012)
As a critical intervention in the history of the novel (and the history of ideas), Srinivas Aravamudan's Enlightenment Orientalism aims to provide an alternative account of the emergence of the novel. To Aravamudan, the majority of the dominant accounts have ignored the role played by less favoured genres such as the Oriental tale in the gestation and development of the novel. Aravamudan's sophisticated readings of a remarkable number of eighteenth-century English and French prose fictions challenge and redress this negligence by demonstrating the different ways in which the Oriental tale, as a vehicle for Enlightenment thought, not only fertilized fiction but, more importantly, disseminated xenophilia and cosmopolitanism in eighteenth-century Europe.